P145 A DUAL CARDIAC COMPLICATION FOR … COMBINATION CHEMOTHERAPY FOR KIDNEY CANCER. (18th May 2022) - Parodi, A; Brunacci, M; Pestelli, S; Merello, M; Lupi, G
Abstract: We present the case of a 66–year–old patient suffering from metastatic kidney cancer who came to the emergency room complaining of dyspnea. 10 days prior to the event, the patient had received the last administration of chemotherapy which consisted of the combination of pembrolizumab (a monoclonal antibody) and axitinib (a tyrosine kinase inhibitor). The cardiological checks carried out up to that moment had not shown changes in the heart. In the emergency room ECG showed the presence of a sinus rhythm with a complete block of the right branch and no signs of ischemia were evident; blood chemistry tests showed an increase in troponin and BNP values. Echocardiography showed moderate left ventricular dysfunction. Therapy with diuretics, beta–blockers and Ras inhibitors was initiated which allowed for rapid resolution of symptoms. At a follow–up five days later the patient presented asymptomatic but with diffuse inversion of the T waves, a new elevation of troponin and more surprisingly the echo showed, in the presence of moderate left ventricular dysfunction, a mobile formation at the level of the apex of the left ventricle. Unfractionated heparin therapy was initiated since, on the basis of echocardiographic characteristics, the diagnosis appeared to be that of thrombosis and chemotherapy was suspended. In the following days the echo did not reveal any modification of the neoformation therefore in consideration of the characteristics (size and high degree of mobility) and of the oncological prognosis of more than one year we decided to initiate the patient to cardiac surgery for the removal operation. The histological analysis of the neoformation confirmed the thrombotic nature. Repeated echocardiography 15 days after surgery showed an almost complete recovery of the ejection fraction. To our knowledge, tyrosine kinase inhibitors can cause ventricular dysfunction (apoptosis) but, in general, it is not an acute event. Pembrolizumab has caused cases of acute myocarditis requiring discontinuation of therapy. As for the origin of the thrombosis the causes are not clear, it could be an effect of left ventricular dysfunction for myocarditis but it cannot be excluded that it is secondary to the use of one or both chemotherapy drugs.